Kajian Terhadap Upaya Perlindungan Hukum Preventif terhadap Merek Dagang di Indonesia Berdasarkan Undang-Undang Nomor 20 Tahun 2016 tentang Merek dan Indikasi Geografis - Lekosono, Arrum Budi; Isradjuningtias, Agri Chairunisa; Anshary, Muhammad Ridha (HUMANIORUM, 2023)
The importance of legal protection for trademarks in Indonesia is reflected in the preventive measures regulated by Law Number 20 of 2016 concerning Marks and Geographical Indications. This study analyzes the implementation of preventive legal protection with a focus on trademark registration. Normative analysis methods and literature study approaches are used to examine the roles and constraints in implementing this preventive measure. In Indonesia's trademark protection context, a preventive legal approach plays an important role in preventing trademark rights infringement. With reference to Law Number 20 of 2016 concerning Marks and Geographical Indications, preventive efforts in the form of registering a mark at the Ministry of Law and Human Rights (HAM) as well as the obligation of trademark holders to fulfill formal and substantive requirements form the basis for providing exclusive protection for brands. Through registration, brand holders obtain legal certainty that secures their exclusive rights. Furthermore, the practical implementation of this preventive protection also requires improving the quality of human resources in related institutions, as well as mastery of foreign languages and the application of technology to minimize opportunities for trademark rights violations.